Emergence and physiological behavior of provenances of pinhão manso in function of level of aluminum - Leandro Henrique de Sousa Mota; Silvana de Paula Quintão Scalon; Daiane Mugnol Dresch; Cesar José da Silva (Bioscience Journal, 2020)
The aluminum in high levels in the soil affects the emergence, growth, and development of various species. Therefore, the objective of this study was to evaluate the emergence and physiological behavior of four provenances of Jatropha curcas subjected to different levels of aluminum. The experiment was performed in a greenhouse in a completely randomized design, with four levels of aluminum in the soil (8.2, 16.5, 24.0 mmolc·dm-3 and control) and four provenances of J. curcas seeds (P1 = Dourados-MS, P2 = Montes Claros-MG, P3 = Alta Floresta-MT, and P4 = Petrolina-PE); the effects of aluminum toxicity were investigated in 25, 50, 75, and 100 days after emergence. The levels of aluminum in the soil were collected from the initial soil correction, which featured an aluminum level of 24.0 mmolc dm-3. The seedling emergence was not affected by treatment with aluminum; however, the height and leaf area of P1, P2, and P3 were reduced with increasing levels of aluminum. The emergence and vigor of J. curcas seeds were not influenced by the differences in the origins of the seeds or by the aluminum levels evaluated. Gas exchanges were affected negatively by aluminum and the responses of the chlorophyll a fluorescence indicate harmful effect in the photosynthetic apparatus. The seeds of origin P4 (Petrolina-PE) has increased tolerance to stress conditions.